National Identity and Market Freedoms after the Treaty of Lisbon - Siniša Rodin (Croatian Yearbook of European Law and Policy, 2011)
The aim of this paper is to explore the balance between market freedoms and national regulatory autonomy following the entry into force of the Treaty of Lisbon, particularly in the light of the rephrased national identity guarantee under Article 4(2) TEU. The paper will discuss whether the newly established obligation of the European Union to respect the national identities of its Member States has any consequences in the case law of the European Court of Justice. Arguably, defining the proper scope of application of the national identity guarantee is relevant to the application of EU law, since it disturbs the previously established balance between European and national law. If defined too broadly, it can undermine the uniform application and effectiveness of EU law. If defined too narrowly, it would be devoid of any useful effect.